2017
DOI: 10.1016/j.irfa.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The financial economics of white precious metals — A survey

Abstract: This article provides a review of the academic literature on the financial economics of silver, platinum and palladium. The survey covers the findings on a wide variety of topics relation to the White Precious Metals including Market Efficiency, Forecastability, Behavioral Findings, Diversification Benefits, Volatility Drivers, Macroeconomic Determinants, and their relationships with other assets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 174 publications
(153 reference statements)
1
28
0
Order By: Relevance
“…Second, our study is motivated by a relative dearth of systematic literature reviews in finance. While systematic reviews become very popular in medical science, psychology, neuroscience, as well as in economics, international business and management, in finance the preference was given to more narrative literature surveys (for example, O'Connor et al [2015]; Vigne et al [2017]). Systematic analysis approaches can provide a more comprehensive understanding of the knowledge in the field, and the findings can change future directions of the research in this discipline by uncovering gaps in the literature.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Second, our study is motivated by a relative dearth of systematic literature reviews in finance. While systematic reviews become very popular in medical science, psychology, neuroscience, as well as in economics, international business and management, in finance the preference was given to more narrative literature surveys (for example, O'Connor et al [2015]; Vigne et al [2017]). Systematic analysis approaches can provide a more comprehensive understanding of the knowledge in the field, and the findings can change future directions of the research in this discipline by uncovering gaps in the literature.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…More specifically, gold provides security since it is a reserve asset of the central banks, and there is no credit risk in investing in gold-based assets. Given that stock markets are labelled as risky assets, gold is a safe asset to invest in ( Vigne et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a comparative analysis which aimed to address the question that if Bitcoin is better safe-haven than gold and commodities, Shahzad et al (2019) concluded that these kinds of assets are weak safe-haven for the global equity indices. In a study on overview of precious metals, Vigne et al (2017) argued that the silver and gold had attracted the focus of researchers, however, it also acknowledged that silver, platinum and palladium do form a single asset class of homogeneous and interchangeable metals. Concerning gold, a comprehensive study by O'Connor et al (2015) surveyed the literature on gold and concluded that gold had been an important investment class.…”
Section: Introductionmentioning
confidence: 99%